Consumers' consumption practices of ready-to-eat foods and food safety knowledge - Robin, Tunung (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
The purpose of this study was to examine consumers’ consumption practices of ready-to-eat foods and their food safety knowledge. Convenience sampling was done by giving questionnaires to 258 ready-to-eat food consumers in Klang Valley, Kuala Lumpur, Malaysia. Based on the results, the biggest motivator for consumers to purchase RTE foods was convenience (47.3%). Most respondents (40.7%) consume RTE foods more than twice a week, and purchased RTE food at restaurants and cafes (36.8%). A majority (54.3%) of the respondents purchased RTE foods for their lunch, and spent RM11-RM20 per person (48.1%). Overall, the respondents had good food safety knowledge. A majority (81%) knew that diarrhea is the common symptom of foodborne disease, and knew about the correct temperature for refrigeration (42.2%). Most of the respondents knew that bacteria will grow quickly at body temperature (36.4%), and that room temperature encourages multiplication of bacteria (66.7%). Respondents knew that raw and cooked food should be separated to prevent transfer of bacteria (60.9%), and that placing raw meat in the plastic bag before putting it into the grocery basket decreases chance of foodborne illness (62%). However, not many respondents (10.1%) knew that the best way to clean a cutting board after using it for raw meat is by washing with bleach and water. This study could help RTE food marketers gain better insights into consumers’ attitude and behavior patterns towards RTE food. Knowing the baseline knowledge of consumers in food safety is essential for the development of effective educational health?